Management Of Village Fund Allocation From The Perspective Of Good Governance (A Study on Equitable Development in Nusa Agung Village, Belitang III District, Ogan Komering Ulu Timur Regency) - I Gusti Made Darma,; Rindy Putri Hapsari,; Catarina Hariyani,; Adie Nurjana Resma, (Jurnal ISO: Jurnal Ilmu Sosial, Politik dan Humaniora, 2024)
This research focuses on the Management of Village Fund Allocation (ADD) from the Perspective of Good Governance (A Study on Equitable Development in Nusa Agung Village, Belitang III District, Ogan Komering Ulu Timur Regency) and the factors influencing the management of Village Fund Allocation (ADD) from the same perspective. The research employs a qualitative method. Based on the findings and data analysis conducted by the researcher, the management of Village Fund Allocation (ADD) from the perspective of Good Governance (A Study on Equitable Development in Nusa Agung Village, Belitang III District, Ogan Komering Ulu Timur Regency) has been implemented fairly well. This is evident from the implementation process, which aligns with the principles of Good Governance, such as community participation in various village programs. The transparency provided is also quite good and effective, such as disseminating extensive information about the village budget through publicly displayed budget boards. The accountability to the community is fairly adequate, although not yet fully optimal, as there are still limitations in access to information regarding the expenditure of the budget.